2011
DOI: 10.1002/hed.21660
|View full text |Cite
|
Sign up to set email alerts
|

Novel neoadjuvant immunotherapy regimen safety and survival in head and neck squamous cell cancer

Abstract: Background Cellular immune suppression is observed in head and neck squamous cell cancer (HNSCC) and contributes to poor prognosis. Restoration of immune homeostasis may require primary cell-derived cytokines at physiologic doses. An immunotherapy regimen containing a biologic, with multiple-active cytokine components, and administered with cytoxan, zinc, and indomethacin was developed to modulate cellular immunity. Methods Study methods were designed to determine the safety and efficacy of a 21-day neoadjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 22 publications
0
51
0
3
Order By: Relevance
“…[56][57][58] Recent approaches tried to modulate immune response by directly targeting molecules involved in the interactions between cancer and the immune system. In particular, several experimental pieces of evidence have demonstrated that Treg eradication by chemical drugs or specific antibodies is a promising strategy to induce a significant anticancer immune response.…”
Section: Immune Therapy: a New Promising Strategy For Hnscc Treatmentmentioning
confidence: 99%
“…[56][57][58] Recent approaches tried to modulate immune response by directly targeting molecules involved in the interactions between cancer and the immune system. In particular, several experimental pieces of evidence have demonstrated that Treg eradication by chemical drugs or specific antibodies is a promising strategy to induce a significant anticancer immune response.…”
Section: Immune Therapy: a New Promising Strategy For Hnscc Treatmentmentioning
confidence: 99%
“…In all cultures, both CD8þ and CD4þ T cells grew out (CD4/CD8 ratio median 2.45, average 5.1 and range 0. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The composition of T cells was not clearly influenced by the culture conditions (Fig.…”
Section: Hpv-specific T Cells Can Be Isolated From Oropharyngeal Tumomentioning
confidence: 99%
“…13,14 In HNSCC a number of cytokine-, antibody-and vaccinebased immunotherapeutic approaches have been tested or are currently underway. [15][16][17] Recently, clinical success was achieved in the field of the immunotherapy of HPV16-induced (pre-) malignancies of the anogenital region, in particular with therapeutic vaccines. [18][19][20] Similar vaccine approaches are tested for the treatment of p53-overexpressing cancers.…”
mentioning
confidence: 99%
“…Subsequently, a cGMP biologic agent designated IRX-2, in combination with the above-described regimen, was explored under corporate sponsorship in the US. A Phase I clinical trial was opened in 2003 and a multicenter Phase 2 trial was recently completed, and results for both studies published [19, 20]. …”
Section: Introductionmentioning
confidence: 99%